Separation and Identification of Hazardous Metal Ions from Different Water Samples By Thin Layer Chromatography: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For separation of metal ions such as Cr ( VI), Cr ( III), Ni ( II), Co (II), Cu(II), Fe(II), Fe(III), Zn(II) and Mo(VI), from two, three and four-component mixtures, thin-layer chromatographic method has been created. The separation was conducted using aqueous humic acid as a mobile process on a thin layer of silica gel 'G.' The chromatographic conduct of metal ions in surfactant mixed resolvents was examined with thin Silica Gel-G layers. The influence of humic acid production in different amounts on the sensitivity of metal captions was also explored. There were also powerful and weak electrolytes and surfactant concentration, an acidity influence and simple aqua surfactant. Metal ions including Cu2 +, Hg2 +, W6 + and Ni2 + were isolated from their binary mix by utilising surfactants and different additives combined in mobile phases. Semi-quantitative Ni2 + calculation was attempted through spot field measurements.